Field notes contributed by Stephen J. Dinsmore, fall 1986 - Iowa State University. Special Collections and University Archives (curator); Dinsmore, Stephen J. (contributor) (1986)
Dinsmore notes the excellent fall migration and shorebird habitat at Saylorville Lake and northern Polk County. He lists numerous bird sightings made by himself and others across Iowa, noting he personally saw 263 species during the fall season. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed